Acompañamiento pedagógico y su incidencia en el rendimiento académico de los estudiantes del 5to año de EGB de la Escuela Victor Manuel Villamarín Gómez, Quinsaloma 2023 - Torres García, Tahína Aneth (2023)
The reason why this research topic was studied is because for many years the problem has arisen in the pedagogical support for the academic performance of students, therefore, this seemed to us to be a topic to be addressed to study in depth, since that in education it is essential to provide and make students aware of quality learning. Pedagogical accompaniment are work guides for the teacher, in these the teacher learns through a mediator with more experience, how to improve their pedagogical practices, which is essential since the academic performance of the students depends on them. Its purpose is to present various ideas and strategies so that the teacher can implement them in the classroom, knowing that not all children learn at the same pace, which is why they must always have different strategies. Currently, it has been evident that many teachers need to have pedagogical support, carried out by authorities of the institution with greater knowledge, carried out in various meeting sessions, in order to guide them. The teacher has the need to always be oriented, this serves for his teaching improvement, in addition to that he always has to be linking his classes with adequate planning and making the respective use of strategies, teaching materials to make the student understand, being clear that each student has a different learning pace.